A fatal case of fungemia due to Fusarium thapsinum in a patient with lung cancer - Marcos-Rodríguez, Raquel; Sobrino-Gómez, Paloma; Alcázar-Fuoli, Laura; Alastruey-Izquierdo, Ana; Ceballos-Atienza, Rafael; Cobo, Fernando (MDPI, 2025)
Fusarium thapsinum is an uncommon cause of invasive fungal disease. Only one case of a hematological patient has been described previously. Most of cases of Fusarium infection is keratitis affecting healthy people, but fungemia is usually produced in immunossupressed patients, especially in those with neutropenia and/or hematological malignancies. The treatment of this infection is difficult due to the fact that these fungi show high MICs to almost all antifungal drugs. We report a case of F. thapsinum fungemia with a fatal outcome, in a patient with lung cancer. The patient developed fever, mucositis and fungemia, and she rapidly worsened and died as a consequence of this infection.